Features of folate cycle disorders in children with ASD (Bangladesh Journal of Medical Science, 2020)
Aim: to show the effect of genetically determined folate cycle deficiency in children with autism spectrum disorders (ASD).Participants: 89 children (57 boys; 32 girls, Ukraine, 2-10 years old); participants were diagnosed with ASD. The control group consisted of 34 children with ASD.Diagnostic methods:polymerase chain reaction (PCR), complex immunological research, diagnosis of infection, determination of biomarkers.Results and discussion:Hyperhomocysteinemia was revealed in 87% of cases (p